1991
DOI: 10.1007/bf00588036
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord tumors: gadolinium-DTPA-enhanced MR imaging

Abstract: To assess the utility of gadolinium-DTPA (Gd) and of MR imaging in the evaluation of spinal cord tumors, ten consecutive patients were prospectively evaluated. T1-proton density-, and T2-weighted images were obtained in sagittal or axial planes. T1-weighted images were obtained before and after intravenous administration. Five tumors were within the cervical spinal cord; 3 neoplasms were within the thoracic cord; 1 neoplasm extended from the cervical to the thoracic cord and 1 neoplasm extended from the cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Reported contrast enhancement of all the intradural spinal tumors in their study. This contrast enhancement also supports the observations of Dillon et al [9], Chamberlain et al [12] and Sze et al [11,15] in that all of the intramedullary spinal tumors in their studies became enhanced after administration of gadolinium contrast material. Intramedullary tumors enhance with contrast media due to breakdown of blood-cord barrier [10].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Reported contrast enhancement of all the intradural spinal tumors in their study. This contrast enhancement also supports the observations of Dillon et al [9], Chamberlain et al [12] and Sze et al [11,15] in that all of the intramedullary spinal tumors in their studies became enhanced after administration of gadolinium contrast material. Intramedullary tumors enhance with contrast media due to breakdown of blood-cord barrier [10].…”
Section: Discussionsupporting
confidence: 87%
“…Direct acquisitions acquired in multiple planes coupled with the ability to study the spine with different T1-and T2-weighted images have enabled critical assessment of the spinal cord and its surroundings not previously available to the medical imaging specialist. The development of contrast media has further extended the capability of MR imaging of the spinal cord by improving its sensitivity [12]. With the advent of MRI, it has been easier to diagnose these lesions preoperatively accurately [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although some have suggested that the absence of contrast enhancement does not necessarily exclude the possibility of intramedullary neoplastic lesions, 24 only a few authors have reported cases of histologically proven nonenhancing spinal tumors. 42 Failure to enhance after contrast administration seems to be a characteristic of tumors associated with significant hemorrhagic components. For instance, although metastatic tumors of the CNS almost always exhibit contrast enhancement, 43 this enhancement is occasionally minimal to absent in metastatic CNS tumors associated with significant hemorrhage.…”
Section: Contrast Enhancement In Intramedullary Spinal Ependymomasmentioning
confidence: 99%
“…90% of all intramedullary tumors; however, because of the lack of specific imaging patterns, reliable differentiation between these 2 common intramedullary tumors can be very difficult, if not impossible. [1][2][3][4][5][6] With recent advances in neurosurgical techniques, ependymomas, because they can be surgically cured in most cases, carry a much better prognosis than astrocytomas. MRI, especially contrast-enhanced imaging, not only shows the exact locations and extensions of intramedullary tumors but also allows the differentiation of tumor cysts compared with tumor-related benign fluid collection.…”
mentioning
confidence: 99%